Mapping the Linguistic Survey of colonial India, 1886-1936 - Jagessar, Philip (2021)
This thesis examines the Linguistic Survey’s mapping of languages in India under George Grierson. Proposed at the 1886 International Congress of Orientalists, the first decade was spent trying to convince the national and provincial governments in India to finance and assist the Linguistic Survey, which saw Grierson deploying several arguments why it would be in the state’s interest to map language. The first chapter outlines those reasons and then demonstrates how the LSI mobilised an informal network of ‘surveyors’ to map India’s languages under seven years. The second chapter studies the maps themselves, looking at the ways in which the LSI tried to overcome the difficulties of mapping something as mutable and inconsistent as language. The diverse range of maps in the LSI suggests that it experimented with different ways of mapping, to avoid the problem of language maps being interpreted as showing defined geographies and ‘hard and fast’ boundaries. The final chapter considers how the LSI’s map of Oriya was deployed by a linguistic movement pushing for statehood as an established and unequivocal geographical reality, contrary to Grierson’s written explanation of what a language map could, and could not, represent.